Anti-parietal cell autoimmunity is associated with an accelerated decline of lung function in IPF patients. (February 2018) - Beltramo, Guillaume; Thabut, Gabriel; Peron, Nicolas; Nicaise, Pascale; Cazes, Aurélie; Debray, Marie-Pierre; Joannes, Audrey; Castier, Yves; Mailleux, Arnaud A.; Frija, Justine; Pradère, Pauline; Justet, Aurélien; et al.
Abstract: Background: Autoantibodies against lung epithelial antigens are often detected in patients with Idiopathic Pulmonary Fibrosis (IPF). Anti-Parietal Cell Antibodies (APCA) target the H+/K+ATPase (proton pump). APCA prevalence and lung H+/K+ATPase expression was never studied in IPF patients. Methods: We retrospectively collected clinical, lung function and imaging data from APCA positive patients (APCA+IPF) and compared them with APCA negative IPF patients matched on the date of diagnostic assessment. H+/K+ATPase expression was assessed with immunohistochemistry and PCR. Results: Among 138 IPF patients diagnosed between 2007 and 2014 and tested for APCA, 19 (13.7%) APCA+ patients were identified. APCA+IPF patients were 16 men and 3 women, mean age 71 years. The median titer of APCA was 1:160. A pernicious anemia was present in 5 patients and preceded the fibrosis in 3 cases. With a mean follow up of 31 months, 2 patients had an exacerbation and 7 patients died. As compared with 19 APCA- IPF patients, APCA+IPF patients had a less severe disease with better DLCO (57% vs 43% predicted), preserved PaO2 (85 ± 8 mmHg vs 74 ± 11 mmHg), a lower rate of honeycombing on HRCT (58% vs 89%), but they experienced an accelerated decline of FVC (difference 61.4 ml/year; p = .0002). The H+/K+ATPase was strongly expressed by hyperplastic alveolar epithelial cells in the fibrotic lung. Conclusion: Anti-parietal cell autoimmunity is detected in some IPF patients and is associated with an accelerated decline of lung function. Anti-parietal cell autoimmunity may promote lung fibrosis progression. Highlights: Recent data indicate that there is an ongoing immune activation in IPF. The proton-pump is expressed by alveolar epithelial cells in the fibrotic lung. Auto-immunity targeting the proton pump is observed in a subgroup of IPF patients. Anti-parietal cell antibody detection associates with an accelerated decline of lung function.